Cat care - Abdullah, Sholehah; Mohd Ghani, Nor Hamiza; Mohammed, Noor Hafiza; Mohamad Yusof, Hani Sakina (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
I have had pets for as long as I can remember. All ups and down, the good and the bad was a worthwhile experience. Let me tell you about my cats, Jacq and Loki. Jacq is six years old Kinkalow. Kinkalow is a curly-eared munchkin. I have him before I have my biological son, Nuh Irfan. So, basically Jacq is also my son, my sweetheart, and my everything. Jacq's son is Loki. He is four years old. Loki was originally terrified of people and would not be petted, even by me. What is the reason for this? Because he is the same age as my son Nuh Irfan. I was preoccupied with becoming a first-time mother when he was born.